Autofluorescence pattern of parathyroid adenomas. Issue 1 (15th February 2021) - Demarchi, M S; Karenovics, W; Bédat, B; De Vito, C; Triponez, F
Abstract: Background: Primary hyperparathyroidism (pHPT) is a common endocrine pathology, and it is due to a single parathyroid adenoma in 80–85 per cent of patients. Near-infrared autofluorescence (NIRAF) has recently been used in endocrine surgery to help in the identification of parathyroid tissue, although there is currently no consensus on whether this technique can differentiate between normal and abnormal parathyroid glands. The aim of this study was to describe the autofluorescence pattern of parathyroid adenoma in pHPT. Methods: Between January and June 2019, patients with pHPT who underwent surgical treatment for parathyroid adenoma were enrolled. Parathyroid autofluorescence was measured. Results: Twenty-three patients with histologically confirmed parathyroid adenomas were included. Parathyroid adenomas showed a heterogeneous fluorescence pattern, and a well defined autofluorescent 'cap' region was observed in 17 of 23 specimens. This region was on average 28 per cent more fluorescent than the rest of the adenoma, and corresponded to a rim of normal histological parathyroid tissue (sensitivity and specificity 88 and 67 per cent respectively). After resection, all patients were treated successfully, with normal postoperative values of calcium and parathyroid hormone documented. Conclusion: Parathyroid adenomas show a heterogeneous autofluorescence pattern. Using NIRAF imaging, the majority of specimens showed a well defined autofluorescent portion corresponding to a rim of normal parathyroid tissue. Further studies should be conducted to validate these findings. Abstract : Near-infrared autofluorescence (NIRAF) has recently been used in endocrine surgery to help identify parathyroid tissue. However, there is currently no consensus on whether this imaging technique can help distinguish between normal and abnormal parathyroid glands. This study identified a heterogeneous 28 per cent less autofluorescent pattern of the parathyroid adenoma in primary hyperparathyroidism and the presence of a cap of normal parathyroid tissue that can both aid in intraoperative detection and confirm the resection of a diseased parathyroid gland in primary hypoparathyroidism. Parathyroid adenoma and auto-fluoresce